A new species of Croton (Euphorbiaceae) from the Espinhaço Mountain Range, Brazil - da Silva, Marcos José; Sodré, Rodolfo Carneiro [UNESP] (Magnolia Press, 2024)
We describe Croton espinhacensis, a new species collected in Bahia and Minas Gerais state, related specially to C. harleyi, a species in section C. sect. Geiseleria from the Caatinga Domain of Northeast Brazil by having the same habit and branching pattern of the stem, leaves grouped at the apex of the branches, bisexual thyrses with flowers continuous along the inflorescence axis, and staminate flowers with 11 stamens. Both species are differentiated mainly by the combination of leaf and floral characters, as well as types floral nectaries. The new species has been confused in herbarium collections with C. atrorufus, a species also found in the Espinhaço Moutain Range, probably due to its habit, colors of the branches and, in some cases, ovate leaves which is why we also compared them. Croton espinhacensis is the only one in sect. Geiseleria with indumented anthers, and one of the few species in the entire genus with this character state.
Keywords: Brazilian Flora; Crotoneae; Diversity; endemism; taxonomy